Deep‐Red to Near‐Infrared Thermally Activated Delayed Fluorescence in Organic Solid Films and Electroluminescent Devices. (9th August 2017) - Li, Chenglong; Duan, Ruihong; Liang, Baoyan; Han, Guangchao; Wang, Shipan; Ye, Kaiqi; Liu, Yu; Yi, Yuanping; Wang, Yue
Abstract: The design and synthesis of highly efficient deep red (DR) and near‐infrared (NIR) organic emitting materials with characteristic of thermally activated delayed fluorescence (TADF) still remains a great challenge. A strategy was developed to construct TADF organic solid films with strong DR or NIR emission feature. The triphenylamine (TPA) and quinoxaline‐6, 7‐dicarbonitrile (QCN) were employed as electron donor (D) and acceptor (A), respectively, to synthesize a TADF compound, TPA‐QCN. The TPA‐QCN molecule with orange‐red emission in solution was employed as a dopant to prepare DR and NIR luminescent solid thin films. The high doped concentration and neat films exhibited efficient DR and NIR emissions, respectively. The highly efficient DR and NIR organic light‐emitting devices (OLEDs) were fabricated by regulating TPA‐QCN dopant concentration in the emitting layers.